Pengembangan Sistem Pencarian Sponsorship dan Partnership Berbasis Web - Ana Kusuma Ardani; Denny Sagita Rusdianto; Arief Andy Soebroto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
This sponsorship and partnership search engine was initially designed to bring companies and communities together. Sponsorship is a form of financial support from a company to ensure the success of an upcoming event, which in return will help the company to gain awareness and good image through the event. However, there are many obstacles that communities often encounter. One being the difficulties in finding accurate information of the sponsor. As for the company, in order to settle into an agreement to support an event, must acquire detailed information regarding the event itself and take many factors into consideration. To solve the issues, a website is built to showcase not only a list of sponsors, but also list of events that might need one. That way, the product offer as well as the aim of the event will be shown clearly. This research is conducted using Object Oriented approach, with MVC [Model - View - Controller] design protocol, and will be developed using the waterfall methode. The sytem development will be conducted through MySQL database. The research has been succesfully tested through unit test, integrated test, validation test, and compatibility test. The entire research has been successfully conducted according to the previous design and analysis.